Cultivation and Biological Characterization of Chicken Primordial Germ Cells - Ji,Meng (2016)
The purpose of this work was to investigate the isolation, culture process of chicken gonadal primordial germ cells (PGCs) and study their biological characterization. PGCs were harvested from 5.5-day-old chicken embryonic genital ridges and explanted onto chicken embryonic fibroblasts (CEFs). The results showed that the primary cultivation of chicken PGCs on their own gonadal stroma cells were better than CEFs at first two days for reproduction. The conditioned media supported the growth and colony formation of PGCs for a prolonged time in vitro and maintained a normal diploid karyotype, which were positively stained by alkaline phosphatase (AKP), periodic acid Schiff (PAS) and reacted with anti-SSEA-1, SSEA-3, Oct4, Blimp1 and Sox2. Real-time PCR showed that they expressed the stage specific genes CVH, Blimp1 and Dazl, the stem cell specific genes Sox2, Pouv and Nanog. They also formed the embryoid bodies (EBs). These results suggested that the chicken PGCs cultured in vitro not only had strong self-renewal ability, but also had the potential capability of multi-lineage differentiation.